The costs, effects and cost-effectiveness of strategies to increase coverage of routine immunizations in low- and middle-income countries: systematic review of the grey literature. - Batt, Katherine (World Health Organization, 2004)
Evidence-based reviews of published literature can be subject to several biases. Grey literature, however, can be of poor quality and expensive to access. Effective search strategies also vary by topic and are rarely known in advance. This paper complements a systematic review of the published literature on the costs and effects of expanding immunization services in developing countries. The quality of data on the effectiveness and cost-effectiveness of strategies to increase immunization coverage is shown to be similar across literatures, but the quality of information on costing is much lower in the grey literature. After excluding poorer quality studies from this review we found the quantity of available evidence almost doubled, particularly for more complex health-system interventions and cost or cost-effectiveness analyses. Interventions in the grey literature are more up to date and cover a different geographical spread. Consequently the conclusions of the published and grey literatures differ, although the number of papers is still too low to account for differences across types of interventions. We recommend that in future researchers consider using non-English keywords in their searches.